2006
DOI: 10.1080/03009740600704221
|View full text |Cite
|
Sign up to set email alerts
|

SLC11A1 gene polymorphisms in Korean patients with Behçet's disease

Abstract: The allele 3 and the genotype allele 3/allele 3 of the 5'-promoter (GT)n in the SLC11A1 gene may have a protective effect for the development of BD in the Korean population. Further studies in other populations are required to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In addition to the D543 N variant, the * 55_58delTGTG polymorphism may be functional because such a deletion may interfere with any of the several regulatory elements found in the 3 0 -UTR of the SLC11A1 gene (Ouchi et al 2003). In the present study, the variant allele frequencies of these two polymorphisms (0.11 for both) were similar to the results (0.04-0.18) of previous Korean and Japanese studies (Liu et al 1995;Yang et al 2000;Ouchi et al 2003;Kim et al 2006), but higher than that (0.01) reported in Caucasian populations (Table 1) (Liu et al 1995). In addition, these two polymorphisms were in complete LD (|D 0 | = 1.00 and c 2 = 1.00), which is consistent with the findings of previous Japanese and Korean studies (Yang et al 2000;Shirakawa and Kishi 2000;Ouchi et al 2003;Kim et al 2006).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition to the D543 N variant, the * 55_58delTGTG polymorphism may be functional because such a deletion may interfere with any of the several regulatory elements found in the 3 0 -UTR of the SLC11A1 gene (Ouchi et al 2003). In the present study, the variant allele frequencies of these two polymorphisms (0.11 for both) were similar to the results (0.04-0.18) of previous Korean and Japanese studies (Liu et al 1995;Yang et al 2000;Ouchi et al 2003;Kim et al 2006), but higher than that (0.01) reported in Caucasian populations (Table 1) (Liu et al 1995). In addition, these two polymorphisms were in complete LD (|D 0 | = 1.00 and c 2 = 1.00), which is consistent with the findings of previous Japanese and Korean studies (Yang et al 2000;Shirakawa and Kishi 2000;Ouchi et al 2003;Kim et al 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The SLC11A1 polymorphisms have been previously found to be associated with various inflammatory and infectious diseases (Greenwood et al 2000;Yang et al 2000;Ouchi et al 2003;Zaahl et al 2006;Kim et al 2006). In the present study, only healthy volunteers confirmed to be disease-free by a regular health check-up were included in the control group.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations